2018
DOI: 10.1038/s12276-018-0171-5
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant role of macrophages in stem cell-induced cardiac repair in rats

Abstract: Bone marrow-derived mesenchymal stem cells (BMMSCs) are used extensively for cardiac repair and interact with immune cells in the damaged heart. Macrophages are known to be modulated by stem cells, and we hypothesized that priming macrophages with BMMSCs would enhance their therapeutic efficacy. Rat bone marrow-derived macrophages (BMDMs) were stimulated by lipopolysaccharide (LPS) with or without coculture with rat BMCs. In the LPS-stimulated BMDMs, induction of the inflammatory marker iNOS was attenuated, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Moreover, an intact immune response is essential to achieve any improvement observed in cardiac function when injecting bone marrow derived progenitor cells into infarcted myocardium (261). Furthermore, bone marrow-derived MSCs achieve better improvement in cardiac function, fibrosis, and angiogenesis when administered in combination with co-cultured macrophages in rat MI, the improvements being associated with elevated anti-inflammatory macrophages and gene expression (262). Finally, the inflammatory response per se elicited during and owing to a stem cell-based therapy may be of paramount importance for the beneficial effects of the latter in a diseased heart (263).…”
Section: Exploitation Of Cardiac and Modified Extracardiac Cells And mentioning
confidence: 99%
“…Moreover, an intact immune response is essential to achieve any improvement observed in cardiac function when injecting bone marrow derived progenitor cells into infarcted myocardium (261). Furthermore, bone marrow-derived MSCs achieve better improvement in cardiac function, fibrosis, and angiogenesis when administered in combination with co-cultured macrophages in rat MI, the improvements being associated with elevated anti-inflammatory macrophages and gene expression (262). Finally, the inflammatory response per se elicited during and owing to a stem cell-based therapy may be of paramount importance for the beneficial effects of the latter in a diseased heart (263).…”
Section: Exploitation Of Cardiac and Modified Extracardiac Cells And mentioning
confidence: 99%
“…In GBM, high expression of CD44 was identified in the proteogenomic profiling of GBM tissues [ 23 ] and further classified as a GBM cell surface antigen in a systematic analysis [ 31 ]. Interestingly, this transmembrane glycoprotein can be cleaved and secreted into the vasculatures, suggesting its potential to be developed as a diagnostic marker [ 67 ]. It has been reported that the activation of CD44 by its ligand promotes cancer stem cell-like phenotypes in GBM and increased therapeutic resistance [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown to increase GBM resistance to radiation therapy [ 25 ]. A recent study demonstrated that a soluble CD44 protein secreted by the GBM cells is the link between GBM and neurodegenerative disorders, as it induces neuronal degeneration through the activation of tau pathology in the brain, which is known to be the underlying mechanism of some neurodegenerative disorders such as Alzheimer’s disease [ 26 ].…”
Section: Discussionmentioning
confidence: 99%